2011
DOI: 10.1037/a0025497
|View full text |Cite
|
Sign up to set email alerts
|

So far away from one's partner, yet so close to romantic alternatives: Avoidant attachment, interest in alternatives, and infidelity.

Abstract: Temptation pervades modern social life, including the temptation to engage in infidelity. The present investigation examines one factor that may put individuals at a greater risk of being unfaithful to their partner: dispositional avoidant attachment style. The authors hypothesize that avoidantly attached people may be less resistant to temptations for infidelity due to lower levels of commitment in romantic relationships. This hypothesis was confirmed in 8 studies. People with high, vs. low, levels of disposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
3
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 45 publications
6
81
3
14
Order By: Relevance
“…Regarding the indirect relationship between anxiety and couple and sexual satisfaction via cyber infidelity, several studies focusing on in-person infidelity have already shown that these two variables are related [32] [40] [41] [42]. The results of the present study suggest that the activation of the attachment system is associated with a desire for virtual emotional and sexual experiences, which satisfy anxious individuals' need for love.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Regarding the indirect relationship between anxiety and couple and sexual satisfaction via cyber infidelity, several studies focusing on in-person infidelity have already shown that these two variables are related [32] [40] [41] [42]. The results of the present study suggest that the activation of the attachment system is associated with a desire for virtual emotional and sexual experiences, which satisfy anxious individuals' need for love.…”
Section: Discussionsupporting
confidence: 59%
“…Individuals with attachment insecurity are more inclined to seek out extradyadic sexual encounters [32] [40] [41] [42]. This is especially true for those with extreme attachment-related anxiety [43] [44] [45].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we expected that people low in avoidance would perceive a warm object as spatially close and to respond with increases in affiliative motivation. People with avoidant attachment styles, in contrast, shy away from intimacy and psychologically distance themselves from others (DeWall et al, 2011;Tidwell, Reis, & Shaver, 1996). Thus, we did not expect physical warmth to increase perceptions of spatial proximity for individuals high in avoidance.…”
Section: Introductioncontrasting
confidence: 44%
“…Doing so allows them to publish the initial finding in conjunction with one or more replications (e.g., DeWall et al, 2011;Finkel et al, 2012). To date, scholars have typically used this strategy to publish conceptual rather than close replications (but see Mikulincer, Shaver, Gillath, & Nitzberg, 2005).…”
Section: Pspb and Personality And Social Psychology Review (Pspr)mentioning
confidence: 97%